2008
DOI: 10.1128/jb.00711-08
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lethality with the dut Defect in Escherichia coli Reveals Layers of DNA Damage of Increasing Complexity Due to Uracil Incorporation

Abstract: Synthetic lethality is inviability of a double-mutant combination of two fully viable single mutants, commonly interpreted as redundancy at an essential metabolic step. The dut-1 defect in Escherichia coli inactivates dUTPase, causing increased uracil incorporation in DNA and known synthetic lethalities [SL(dut) mutations]. According to the redundancy logic, most of these SL(dut) mutations should affect nucleotide metabolism. After a systematic search for SL(dut) mutants, we did identify a single defect in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…Deletion of either gene produces perfectly viable cells, while deletion of both is lethal. Other examples of synthetic lethality are found in various aspects of bacterial physiology such as DNA damage and repair (9), cell division (10), outer membrane biogenesis (11), and metabolism (12). It is worth noting that synthetic interactions often involve genes that are not linked on the chromosome and that are not related to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of either gene produces perfectly viable cells, while deletion of both is lethal. Other examples of synthetic lethality are found in various aspects of bacterial physiology such as DNA damage and repair (9), cell division (10), outer membrane biogenesis (11), and metabolism (12). It is worth noting that synthetic interactions often involve genes that are not linked on the chromosome and that are not related to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with rdgB or dut mutants, that have elevated levels of spontaneous chromosomal fragmentation due to, correspondingly, hypoxanthine-DNA or uracil-DNA incorporation and excision, secondary mutations were isolated that made the original single mutants inviable (synthetically lethal with the rdgB or dut defects) (204, 324). Among such RdgB- or Dut-dependent mutants, there were multiple hits inactivating all the known six genes of recombinational repair of double-strand breaks in E. coli : recA , recB , recC , ruvA , ruvB and ruvC (204, 324). The prediction is that, if performed in the recBC sbcA or recBC sbcBC backgrounds, such a screen should yield all other known rec mutants, as well as (hopefully) some still unknown ones.…”
Section: Genetic Analysis Of Hr Reveals Distinct Pathwaysmentioning
confidence: 99%
“…Uracil in DNA can arise by two mechanisms, cytidine deamination and misincorporation of dUTP. Both mechanisms are potentially mutagenic because of the formation of an AP during their repair (2)(3)(4), and it has been shown that a high intracellular concentration of dUTP is toxic in mammalian cells (5), yeast (6,7), and bacteria (8). It is interesting to note that most DNA polymerases do not discriminate dUTP from deoxythymidine triphosphate (dTTP), as shown by in vitro assays (3).…”
mentioning
confidence: 99%